2004
DOI: 10.1136/jech.58.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood deprivation and incidence of coronary heart disease: a multilevel study of 2.6 million women and men in Sweden

Abstract: Study objective: To examine whether neighbourhood deprivation predicts incidence rates of coronary heart disease, beyond age and individual income. Design: Follow up study from 31 December 1995 to 31 December 1999. Women and men were analysed separately with respect to incidence rates of coronary heart disease. Multilevel logistic regression was used in the analysis with individual level characteristics (age, individual income) at the first level and level of neighbourhood deprivation at the second level. Neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
164
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 38 publications
(30 reference statements)
5
164
1
4
Order By: Relevance
“…In sum, women may be more reliant on neighborhood resources or men are more influenced by extra-residential factors, or both. However, other studies have found stronger associations between composite measures of neighborhood disadvantage and mortality among men than among women (Sundquist et al, 2004;Nordstrom et al, 2004). Further exploration is required to ascertain mechanisms driving these differences.…”
Section: Discussionmentioning
confidence: 91%
“…In sum, women may be more reliant on neighborhood resources or men are more influenced by extra-residential factors, or both. However, other studies have found stronger associations between composite measures of neighborhood disadvantage and mortality among men than among women (Sundquist et al, 2004;Nordstrom et al, 2004). Further exploration is required to ascertain mechanisms driving these differences.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, employed women had higher odds (1.45, p=0.002) of being overweight or obese compared to their unemployed counterparts. Several theories have been postulated on the possible relationships between income and weight, which are positive, negative or inverted U-shaped [41,46,49]. Demand for food that raises weight could increase with increase in income.…”
Section: Discussionmentioning
confidence: 99%
“…In general, this research has shown significant neighborhood-level effects after "adjustment" for potential confounding factors including individual-level socioeconomic status/position. 4,[6][7][8][9][10] This area of research is particularly germane to women as previous work suggests that residence in a deprived neighborhood may affect the cardiovascular health of women to a greater extent than men. 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…7 Using a neighborhood medical care need index, Sundquist et al reported odds ratios among adults in the most versus the least deprived neighborhoods of 1.9 and 1.4 for women and men, respectively, after adjustment for individual-level age and income (14,259 events). 6 Neither of these studies examined neighborhood-level effects on CHD across a broad array of sociodemographic groups, tested for differences by gender, or examined effects on case fatality, an indicator of severity of disease and quality of care. Separate studies have examined the relationship between area-based measures and case fatality/survival following an acute myocardial infarction 11-15 and while all found significant associations, only one presented neighborhood results separately by gender, 12 and none presented case fatality from overall CHD.…”
Section: Introductionmentioning
confidence: 99%